Effect of Intrasexual Competition Threats on Sexual Orientation Prejudices - Vermiglio, Nick A.; Vossen, Taylor J.; Rusten, Marta L.; Ruder, Andrea S. (My University, 2014)
The affordance management perspective (e.g., Neuberg et al., 2011) suggests that human cognition and behavior serve to manage the potential threats and opportunities in the social environment. Applied to sexual orientation prejudices, emotional and behavioral reactions arise from perceptions that some sexual orientation groups pose certain threats or opportunities to the perceiver. The purpose of this study was to combine the affordance management and fundamental motives approaches to examine how perceived threats and opportunities driving sexual prejudices shift as a function of different fundamental motives of the perceiver.
Color poster with text and graphs.
Keywords: Posters; Sexual prejudice